The health effects of agricultural pesticides: are farmers willing to pay? - Bakti Hasan-Basri,; Aina Faieqah Zabri,; Junaidah Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The objective of this study is to estimate farmers' Willingness to Pay (WTP) to reduce the health impacts of pesticide use in rice cultivation in Perlis, Malaysia. The Double-Bounded Contingent Valuation Method was used to estimate the WTP value. A total of 150 respondents were interviewed and distributed according to the number of farmers registered with a Malaysian Agricultural Development Authority, MADA. The results show that four variables, namely gender, education level, income level, and pesticide exposure, are statistically significant in explaining respondents' WTP for safer pesticides. Of these four variables, only gender has a negative sign. Since males represented gender, the negative sign means that male farmers were willing to pay less than female farmers. The results also show that farmers' education level and income have a positive impact on their WTP. Farmers with a higher level of education have a better understanding of the impact of pesticides on human health. Therefore, they have more awareness of reducing these risks, which can be achieved through higher prices for safer pesticides. The positive sign of the income variable indicates that the probability of respondents switching to the use of safer pesticides is positive as their income increases. Respondents are willing to pay a maximum of RM10.22 for safer pesticides. This study extends the existing literature on the impact of pesticides on agriculture by focusing on the monetary value of reducing the health impacts of pesticide use. It also identifies farmers' WTP for safer pesticides. This study has a reference value for safer pesticide use in agriculture. Agencies involved in rice cultivation particularly in Malaysia can benefit from the results of this study. The WTP value can be used as a benchmarking value to improve the current subsidy program for farmers.